2012
DOI: 10.1016/j.virol.2012.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hepatitis C virus release by the interferon-induced protein BST-2/tetherin

Abstract: Hepatitis C virus is a leading cause of chronic hepatitis and liver cancer. Little information exists on the interplay between innate defense mechanisms and viral antagonists that promote viral egress. Herein, the effects of Tetherin/BST-2 on HCV release were investigated. In Huh-7.5 hepatocytes, low expression levels of BST-2 were detected. Treatment of Huh-7.5 cells with IFNα, elevated BST-2 expression levels. However, HCV could not alter the expression of IFNα-induced BST-2, nor of stably over-expressed BST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 83 publications
1
31
0
Order By: Relevance
“…This suggests the BST2‐triggered tethering of budding virions to vesicle membranes that remain on cell surfaces at the plasma membrane after exocytosis . BST2 has been described as moderately restricting the release of the hepatitis C virus, whose assembly takes place in the ER and whose release from cells via secretory pathways occurs in a manner similar to that of coronaviruses . Combined, these data support the assumption that enveloped virus budding and release occurring at the plasma membrane or in an intracellular compartment is subject to BST2 blocking.…”
Section: Introductionmentioning
confidence: 56%
“…This suggests the BST2‐triggered tethering of budding virions to vesicle membranes that remain on cell surfaces at the plasma membrane after exocytosis . BST2 has been described as moderately restricting the release of the hepatitis C virus, whose assembly takes place in the ER and whose release from cells via secretory pathways occurs in a manner similar to that of coronaviruses . Combined, these data support the assumption that enveloped virus budding and release occurring at the plasma membrane or in an intracellular compartment is subject to BST2 blocking.…”
Section: Introductionmentioning
confidence: 56%
“…However, some enveloped viruses such as herpesviruses (which complete their final envelopment by obtaining membranes from TGN and/or endosomal compartments and egress via exocytosis), are also subject to BST2 restrictions Mansouri et al, 2009;Mettenleiter, 2002). Results from one recent study suggest that BST2 can moderately restrict the release of hepatitis C virus (HCV), whose assembly takes place in the ER, and whose release from cells occurs via secretory pathways in a fashion similar to that of coronaviruses (Dafa-Berger et al, 2012;Jones and McLauchlan, 2010). It is possible that virions linked to vesicle membranes via BST2 association are retained on cell surfaces following the exocytotic fusion of virion-containing vesicles with plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
“…IFN induces the expression of lncRNA BST2 or BISPR in several cell lines (Kambara et al, 2015; Barriocanal et al, 2015). BISPR is located head-to-head with BST2/tetherin, a well-characterized antiviral factor that attaches viruses to the cell surface and impedes viral release (Dafa-Berger et al, 2012; Neil et al, 2008). Both BISPR and BST2 are corregulated and it has been shown that BISPR acts in trans to induce transcription of BST2 gene, probably, by counteracting the repressive action of PRC2 (Kambara et al, 2015; Barriocanal et al, 2015).…”
Section: Viruses and Lncrnasmentioning
confidence: 99%